Why food safety matters to Africa: Making the case for policy action - Jaffee, S.; Henson, S.; Grace, Delia; Ambrosio, M.; Berthe, F. (International Food Policy Research Institute, 2020)
Food safety is vital for achieving food and nutritional security in Africa. Unsafe food contains microbiological, chemical, or physical hazards that can make people sick, causing acute or chronic illness that, in extreme cases, can lead to death or permanent disability.2 The presence of foodborne hazards can also reduce the bioavailability of nutrients in food, putting already food-insecure populations at greater risk of malnutrition. Food safety is closely linked to other food-related public health issues. For example, the inappropriate use of antimicrobials in livestock and aquaculture production is contributing to the emergence of antimicrobial-resistant pathogens.